Clinical Outcome of Pars Plana Vitrectomy With Or Without Intravitreal Bevacizumab As A Pretreatment in Advanced Diabetic Eye Disease: Doi:10.36351/pjo.v36i4.1036 - Gull, Ambreen; Ahmad, Sairam; Khan Niazi, Fuad Ahmad; Raza, Ali (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find out the clinical outcome of Pars Plana Vitrectomy with and without Intravitreal Bevacizumab as a pretreatment in advanced diabetic eye disease. Place and Duration of Study: Ophthalmology department of holy family hospital Rawalpindi, from January 2018 to December 2018. Methods: Sixty patients with advanced proliferative diabeticretinopathy wereincluded. Patients were divided into two groups. In group A, patients had pars plana vitrectomy with pre procedure injection of intravitreal Bevacizumab and group B had vitrectomy without pre procedure intravitreal Bevacizumab. Amount of bleeding during vitrectomy, surgical time and rate of iatrogenic tears were noted in both groups. Outcome measures were post operative best corrected visual acuity at 6 months and post operative recurrent vitreous hemorrhage. Results: Patients had a mean age of 63.83 ± 7.314. In group A, mild bleeding was seen in 33%, moderate in 6.7% and severe in 0%. In group B, mild bleeding was seen in 13.3%, moderate in 46.7%, and severe bleeding in 40%. After 6 months, 27 (90%) patients in group A showed improvement in best corrected visual acuity while it was seen in 12 (40%) patients in group B. Iatrogenic tearswere seen in 10% in group A and 36% in group B. Mean time of surgery in group A was 59.27 ± 6.823 minutes and in group B was 77.87 ± 9.637 minutes. Rate of recurrent vitreous hemorrhage after vitrectomy was 6.7% in group A and 40% in group B. Conclusion: Intravitreal injection of Bevacizumab is helpful in reducing surgical time and also decreases intraoperative and post operative bleeding. Key Words: Bevacizumab, Vitrectomy, Proliferative Diabetic Retinopathy.